Atmospheric Circulation Response to Anomalous Siberian Forcing in October 2016 and its Long‐Range Predictability. Issue 5 (6th March 2019) - Tyrrell, Nicholas L.; Karpechko, Alexey Yu.; Uotila, Petteri; Vihma, Timo
Abstract: The warm Arctic‐cold continent pattern was of record strength in October 2016, providing the opportunity to test its proposed influence on large‐scale atmospheric circulation. We find a record weak polar stratospheric vortex and negative North Atlantic Oscillation in November–December 2016 and link them to increased planetary wave generation associated with cold Siberian anomalies followed by troposphere‐stratosphere dynamical coupling. At the same time the warm Arctic anomalies, in particular those over the Barents‐Kara Seas, do not appear to play an important role in forcing the atmospheric circulation. Long‐range forecasts initialized on 1 October 2016 reproduced both the weak polar vortex and negative North Atlantic Oscillation, as well as their link with the Siberian temperatures. Our results support the stratospheric pathway for atmospheric circulation forcing associated with Siberian surface anomalies and uncover a source of skill for subseasonal forecasts from October to December. Plain Language Summary: The warm Arctic‐cold continent pattern is an observed, large‐scale pattern of near‐surface temperatures where the Arctic is warmer than average and Siberia is colder than average. This pattern was of record strength in October 2016, providing the opportunity to test its influence on the Northern Hemisphere atmospheric circulation and the possibility of skillful long‐range forecasts. It has been proposed that the warm Arctic‐cold continent pattern can drive large atmospheric waves, which are able to travel from the troposphere into the stratosphere, where they weaken the strong wintertime winds that make up the stratospheric polar vortex. A weakened polar vortex can then lead to changes in the surface pressure that can affect weather patterns. We find a record weak polar stratospheric vortex in late autumn 2016 and link that to cold Siberian anomalies. At the same time the warm Arctic anomalies do not appear to play an important role in forcing the atmospheric circulation. Long‐range forecasts initialized in October 2016 reproduced both the weak polar vortex and resulting surface pressure patterns. Our results support the stratospheric pathway for atmospheric circulation forcing by Siberian surface anomalies and uncover a source of skill for subseasonal forecasts in the Northern Hemisphere autumn. Key Points: Record strength of October 2016 Warm Arctic‐Cold Continent pattern led to weak polar vortex and negative NAO in November to early December Atmospheric circulation response is attributed to Siberian cold anomalies but not to warm anomalies in the central Arctic Subseasonal range stratospheric response to October 2016 Siberian temperature is reproduced by the ECMWF seasonal forecast model